Frequency magic squares - Hicks, Kenneth; Laywine, Charles F.; Mullen, Gary L. (Utilitas Mathematica, 2002)
If n = λ0 + ⋯ + λm-1, we construct a frequency magic square of order n and partition λ0 + ⋯ + λm-1, expect for the cases when n = 2 = 1 + 1 and n = 3 = 2 + 1, when such frequency magic squares do not exist.